The Footprint of Progressive Women’s Service In Anggana District, Kutai Kartanegara, East Kalimantan - Afriyani; Normawati; Abdul Hopid; Sama Alee, Abdulrahman (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem: The implementation of Community Service in the Muhammadiyah organization brings many benefits and advantages for Muslims in Indonesia in general and Muhammadiyah members in particular. To find out how the contribution and implementation of community service in the field of upholding brotherhood and improving the quality of the community, this study conducted mini research in 2 Muhammadiyah schools in Anggana District, namely TK Aisyiyah Bustanul Athfal 1 Anggana and SD Muhammadiyah 1 Anggana, as well as research was also conducted at the Aisyiyah religious study in Anggana District. Purpose: To find out how the contribution and implementation of community service in the field of upholding brotherhood and improving the quality of the community. Design/methods/approach: The method used to collect data was by interview and observation. Findings: The results obtained were that the 'Aisyiyah study and Muhammadiyah schools in Anggana District have played a significant role in strengthening Islamic brotherhood and shaping students' character. Both have shown consistent efforts in realizing Islamic values in everyday life.